Pengaruh Pengendalian Mutu terhadap Kualitas Produk pada PT Prima Thomas Sejahtera - Agus Purwo Wicaksono; Rizal Rahmawan (Neolectura, 2022)
Control (Quality Control) is all efforts to ensure that the results of the implementation are in accordance with a predetermined plan and satisfy consumers. The purpose of Quality Control is to prevent goods that are not in accordance with the desired quality standards (second Quality) continuously and to be able to control, select, assess quality so that consumers feel satisfied and the company does not suffer losses. The purpose of this study is to determine the effect of quality control on product quality at PT. Prima Thomas Sejahtera. This research is a survey research using descriptive analytical method. Riduwan (2007:275) The population in this study were 40 people from the Quality Control section. The sample in this study were 40 people from the quality control department. Data analysis techniques are linear regression analysis, analysis of the coefficient of determination and partial test (t test). the writer concludes that based on the observation results, the quality control process for product quality carried out by this company is good. And need to be maintained so that quality can continue to be obtained. Indicators of quality control and product quality at PT. Prima Thomas Sejahtera implemented by the company is in line with the theoretical basis according to Rambat and Hamdani (2006:68-73) that quality has eight dimensions of measurement. While the results of the correlation coefficient analysis show that the quality control variable has a significant influence on product quality